Seasonal flow reversals of intermediate waters in the canary current system east of the Canary Islands - Machín, Francisco; Pelegrí, Josep Lluís; Fraile-Nuez, Eugenio; Vélez-Belchí, Pedro; López Laatzen, Federico; Hernández Guerra, Alonso (Journal of Physical Oceanography, 2010)
8 pages, 6 figures, 1 table Two 9-yr current-meter and salinity records, together with climatological data, reveal marked seasonal variability of the intermediate flow at a key location in the Canary Basin. The region is characterized by a summer (July-September) and early fall (October) northward progression of Antarctic Intermediate Water followed by a fall (November-December) intense flow reversal of Mediterranean Water. A Sverdrup-type model confirms that these movements are associated with stretching or shrinking of the intermediate water strata This study has been performed as part of projects CANOA (CTM2005-00444/MAR) and ORCA (CTM2005-04701-C02-01), funded by Spanish Ministry of Science, and by project RAPROCAN, funded by Instituto Español de Oceanografóa. FM was supported by the Juan de la Cierva Programme and by the Postdoctoral Programme of the Universidad de Las Palmas de Gran Canaria Peer Reviewed